Використання слідчим знання криміналістичної характеристики вбивств на "замовлення" при огляді місця події - Корж, В. П.; Korzh, V. P. (Криміналістика і судова експертиза. - 2019. - Вип. 64. - С. 189-200, 2019)
Проведено науковий аналіз криміналістичної характеристики злочинів, розглянуто типові способи вбивств на «замовлення», знаряддя, засоби зазначених вбивств, підготовчі дії «замовника», типові способи приховування вбивства, типові сліди вбивства, сліди на місці засади, типові версії. Обґрунтовано використання слідчим знання криміналістичної характеристики вбивств на «замовлення» при огляді місця події.

The article analyzes the scientific approaches to the conceptual apparatus of forensic characterization of crimes and suggests that the forensic characterization of ‘contract’ murders be considered as a system of significant forensic information about the signs of the preparation of the organizer (‘customer’) to commit a murder, the identity of the perpetrator, the identity of the victim, typical murder methods, the circumstances of its commission, typical traces of a crime, the use of which allows the investigator, taking into account the specific situation determine the inspection tasks of the scene, investigative techniques. The main elements of the forensic characterization of the ‘ordered’ murder are considered. An important element of the forensic characterization is the method of murder, which includes a method of preparing for a crime, a method of committing murder, a method of hiding traces of murder. Knowledge by the investigator of typical methods of murder will contribute to promptness in the search for the murder weapon, the identity of the criminal, traces, physical evidence, the solution of the main tasks of inspecting the scene, and solving the crime in hot pursuit. Forensic knowledge of the investigator on the preparatory actions of the organizer, the stages of the preparation of the ‘customer’ and the executor (killer) of the murder are essential for the investigation of the ‘ordered’ murders. In the process of preparing for the murder, the ‘executor’ plans in advance how to conceal traces of the murder. Identifying and fixing the material traces at the scene of the incident will help the investigator to simulate the ‘trail picture’ of the ‘contract’ murder, to put forward versions of the identity of the perpetrator, the person of the victim. Using the investigator, tactical rules, forensic recommendations when inspecting the scene of the incident will quickly reveal and investigate the ‘ordered’ murder.

В статье проанализированы научные подходы к понятийному аппарату криминалистической характеристике преступлений и предложено криминалистическую характеристику «заказных» убийств рассматривать как систему криминалистической значимой информации о признаках подготовки организатора ( «заказчика») к совершению убийства, личности исполнителя преступления, личности жертвы, типичных способах убийства, об обстановке его совершения, типичных следах преступления, использование которой позволяет следователю с учетом конкретной ситуации определить задачи осмотра места происшествия, методы расследования. Рассмотрены основные элемнты криминалистической характеристики «заказного» убийства. Важным элементом криминалистической характеристики является способ убийства, который включает способ подготовки к преступлению, способ совершения убийства, способ сокрытия следов убийства. Знание следователем типичных способов убийства будет способствовать оперативности в поиске орудия убийства, личности преступника, следов, вещественных доказательств, решению основных задач осмотра места происшествия, раскрытию преступления по «горячим» следам. Существенное значение для расследования «заказного» убийств имеют криминалистические знания следователя о подготовительных действиях организатора, этапы подготовки «заказчика» и исполнителя ( киллера) убийства. В процессе подготовки к убийству «исполнитель» заранее планирует способы сокрытия следов убийства. Выявление и фиксация материальных следов на месте происшествия поможет следователю смоделировать «следовую картину» «заказного» убийства, выдвинуть версии о личности преступника, личности потерпевшего. Использование следователем, тактических правил, криминалистических рекомендаций при осмотре места происшествия позволит оперативно раскрыть и расследовать «заказное» убийство.
The use by the investigator of the knowledge of the forensic characterization of «contract» murders when inspecting the scene
Использование следователем знаний криминалистической характеристики «заказных» убийств при осмотре места происшествия
Keywords: криміналістична характеристика; типові способи вбивств на «замовлення»; підготовчі дії «замовника»; типові сліди вбивства; огляд місця події; forensic characteristic; typical methods of contract killings; preparatory actions of the "customer"; typical signs of murder; inspection of the scene; криминалистическая характеристика; типичные способы убийств «на заказ»; подготовительные действий «заказчика»; типичные следы убийства; осмотр места происшествия